Stability of spray-dried chitosan salts derived from lobster chitin as a raw material - Nilia De la Paz; Caridad García; Mirna Fernández; Lisandra García; Vivian Martínez; Orestes López; Antonio Nogueira (Ars Pharmaceutica, 2015)
Aim: The objective of this work was to develop and validate a method for determining the degree of molar deacetylation of chitosan acetate and chitosan lactate, as well as to study the stability of both salts. Materials and Methods: A spectrophotometric method was validated according to internationally-established quantitative techniques. Three industrial batches of chitosan acetate and chitosan lactate, obtained by spray drying, were stored under shelf life conditions for twelve months. Organoleptic characteristics, the degree of molar deacetylation, pH, loss on drying and microbiological count were determined at the beginning and end of the study. Results and Discussion: The statistical data proved that the two methods complied with international standards for the validation of analytical techniques. It was shown that the procedures developed were linear, specific, precise and accurate, so they can be used for the purposes of quality control and stability study of the polymer salts. Salts remained in powder form, with a light-yellow to dark-yellow coloration. Values of loss on drying (2.5 - 5.2 %) of chitosan salt using acetic or lactic acid, as a solvent, indicated the good quality of spray-dried particles of chitosan. Similar behavior was obtained regarding pH. The two salts stayed within the parameters that determine their quality, both in the initial stage and after twelve months at room temperature. Conclusion: Spray drying chitosan acetate and chitosan lactate, stored at room temperature in a dry place, in double polyethylene bags and multilayer paper bags, kept their physical, chemical and microbiological characteristics for a period of twelve months.